A Look at the Life of the Great Politician, Scientist Faizulla Khojayev and the Activities of the Memorial House Museum (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article contains rich information about the life, path, services of the great thinker, reformer, politician Faizulla Khojayev, as well as the activities of the memorial house-museum located in the city of Bukhara, its expositions, and ongoing research. It is said about dedicated to the decisions and resolutions developed for the development of the museum.